UpayaMeningkatkan Hasil Belajar PKn Melalui Penerapan Model Pembelajaran Jigsaw - Asminah, Asminah (JURNAL GLOBAL EDUKASI, 2017)
Abstract: Classroom action research aims to improve the learning outcomes of third grade students of SD Negeri 014685 Siumbut Baru through the application of Jigsaw learning model on Civics lesson with Recreation theme. This classroom action research was conducted in the third grade of SD Negeri 014685 Siumbut Baru which was 25 students. The subject of this research is the third grade students of SD Negeri 014685 Siumbut Baru. The results of research on the first cycle obtained mastery of student learning outcomes of 73.24% while the second cycle increased to 100%. Can be concluded through the implementation of learning model Jigsaw can increase the learning outcomes of Civics in third grade students SD Negeri 014685 Siumbut Baru Keywords: Jigsaw, recreation Abstrak: Penelitian tindakan kelas bertujuan untuk meningkatkan hasil pembelajaran siswa kelas III SD Negeri 014685 Siumbut Baru melalui penerapan model pembelajaran Jigsaw pada pelajaran PKn dengan tema Rekreasi. Penelitian tindakan kelas ini dilaksanakan di kelas III SD Negeri 014685 Siumbut Baru yang berjumlah 25 orang siswa. Subjek penelitian ini adalah siswa kelas III SD Negeri 014685 Siumbut Baru. Hasil penelitian pada siklus I diperoleh ketuntasan hasil belajar siswa sebesar 73,24% sedangkan siklus II meningkat menjadi 100%. Dapat disimpulkan melalui penerapan model pembelajaran Jigsaw dapat meningkatka hasil belajar PKn pada siswa kelas III SD Negeri 014685 Siumbut Baru Kata kunci: Jigsaw, rekreasi